2005
DOI: 10.1038/sj.onc.1208598
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of p16, RUNX3, and HPP1 occurs early in Barrett's-associated neoplastic progression and predicts progression risk

Abstract: Patients with Barrett's esophagus (BE) are at increased risk of developing esophageal adenocarcinoma (EAC). Clinical neoplastic progression risk factors, such as age and the length of the esophageal BE segment, have been identified. However, improved molecular biomarkers predicting increased progression risk are needed for improved risk assessment and stratification. Using realtime quantitative methylation-specific PCR, we screened 10 genes (HPP1, RUNX3, RIZ1, CRBP1, 3-OST-2, APC, TIMP3, p16, MGMT, p14) for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
200
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(210 citation statements)
references
References 78 publications
7
200
2
1
Order By: Relevance
“…22 Five genes shown to be methylated with increasing grade of dysplasia were tested: p16, ESR1, MYOD1, HPP1, and RUNX3. 21 After reviewing pilot data, only MYOD1 and RUNX3 were taken forward, as these were the most promising (See Appendix, p3).…”
Section: Introductionmentioning
confidence: 99%
“…22 Five genes shown to be methylated with increasing grade of dysplasia were tested: p16, ESR1, MYOD1, HPP1, and RUNX3. 21 After reviewing pilot data, only MYOD1 and RUNX3 were taken forward, as these were the most promising (See Appendix, p3).…”
Section: Introductionmentioning
confidence: 99%
“…HPP1 methylation has also been detected in the dysplastic mucosa of ulcerative colitis patients (Sato et al, 2002). More recently, HPP1 methylation was shown to occur early in Barrett's-associated neoplastic progression to oesophageal adenocarcinoma, and was predictive of progression risk (Schulmann et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] However, evidence supporting its tumor suppressive activity has been lacking. In this current study, we have demonstrated that ectopic expression of HPP1 in the colon cancer cell line, HCT116 results in a distinct alteration in cellular appearance consistent with reversion of transformation morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation of HPP1 has been described in Barrett's-associated esophageal adenocarcinoma, gallbladder cancer, malignant mesothelioma and breast and lung cancer cell lines. [8][9][10][11] From a translational standpoint, there is growing interest in the study of HPP1 as a biomarker in gastrointestinal malignancies. HPP1 was among a panel of genes for which methylated DNA could be detected in the stool of patients with colorectal cancer.…”
mentioning
confidence: 99%